Effects of forward-facing cavity on drag in hypervelocity projectiles: a computational approach - Nagarkar, Kavana; Shetty, Shamitha; Khan, Sher Afghan; Baig, Muneer (Elsevier Ltd Kidlington Corporate Office, Kidlington, United Kingdom, 2026)
The present numerical study examines hypersonic flow (Mach 5.9) over a blunt body, comparing configurations with and without a forward-facing cavity (FFC). Operating at 1200 Pa and 143 K free-stream conditions, the research focuses on critical parameters, including the drag coefficient, pressure fluctuations, and shock stand-off distance, using unsteady-state RANS simulations. The findings indicate that a forward-facing cavity reduces drag by up to 18% at an L/D ratio of 3. This improvement is attributed to an increased shock stand-off distance, which alters the flow dynamics around the body. The s-a turbulence model with three coefficient equations has satisfied the Navier-Stokes equations to simulate hypervelocity flow over a blunt body. The current time-dependent simulation has provided almost steady results after reaching 11 milliseconds. A comparative analysis of blunt bodies with and without cavities, and with varying L/D ratios, further demonstrates that deeper cavities enhance performance in hypervelocity conditions.